Mucosal healing in inflammatory bowel diseases: a systematic review. - Neurath, M; Travis, S (2012)
Recent studies have identified mucosal healing on endoscopy as a key prognostic parameter in the management of inflammatory bowel diseases (IBD), thus highlighting the role of endoscopy for monitoring of disease activity in IBD. In fact, mucosal healing has emerged as a key treatment goal in IBD that predicts sustained clinical remission and resection-free survival of patients. The structural basis of mucosal healing is an intact barrier function of the gut epithelium that prevents translocation of commensal bacteria into the mucosa and submucosa with subsequent immune cell activation. Thus, mucosal healing should be considered as an initial event in the suppression of inflammation of deeper layers of the bowel wall, rather than as a sign of complete healing of gut inflammation. In this systematic review, the clinical studies on mucosal healing are summarised and the effects of anti-inflammatory or immunosuppressive drugs such as 5-aminosalicylates, corticosteroids, azathioprine, ciclosporin and anti-TNF antibodies (adalimumab, certolizumab pegol, infliximab) on mucosal healing are discussed. Finally, the implications of mucosal healing for subsequent clinical management in patients with IBD are highlighted.